Does avoidance of oral exposure to patch test allergens benefit patients with eczema? A systematic review - Louay S Abdulkarim; Emily Ko; Isabella Wolfe; Beatriz Suarez Martinez-Falero; Ying Teo; Emma Corden; Peter S Friedmann; Michael R Ardern-Jones (Skin Health and Disease, 2026)
Abstract Background The increased risk of cutaneous allergies in patients with eczema is well recognized. For recalcitrant cases, patch testing is recommended, and cutaneous avoidance of positive allergens is standard practice. However, some allergens are also present in foods and medicines, but the precise role of dietary avoidance to allergens identified by patch testing in eczema remains unclear. Objectives To evaluate the relationship between oral exposure to patch test-confirmed allergens and eczema provocation. Methods The MEDLINE, Embase and Web of Science databases were systematically searched from inception to 1 March 2025. Studies were included only if the patient cohort was diagnosed with an eczema phenotype (including atopic, dyshidrotic and contact eczema) and the manuscript reported patch test results. Studies were divided into two groups: (i) oral challenge and (ii) dietary avoidance; meta-analyses were undertaken separately. The protocol for this review was registered in PROSPERO (CRD420251112648). Bias was assessed with the RoB 2.0, ROBINS-I and JBI tools for randomized controlled trails, nonrandomized interventional studies and case series, respectively. Evidence quality was graded as per the GRADE criteria. Results Of the 7114 manuscripts identified, 29 studies with a total of 1424 patients were included after applying the inclusion and exclusion criteria, including 13 randomized controlled trials. Seventeen of the 29 were nickel-challenge studies (999 patients) and 78% of patients with nickel allergy had eczema flares when challenged with oral nickel. Similarly, 12 of 29 studies (1003 patients) investigated dietary nickel avoidance and 78% of patients showed improvement of eczema. Nine of 29 studies (149 patients) included dietary study of other allergens including balsam of Peru, aluminium and cobalt; 46% of the sensitized patients responded to either oral challenge or dietary restriction. Conclusions This systematic review provides evidence to suggest that patients with eczema benefit from reduced oral exposure to positive patch test allergens. The strongest evidence of benefit was with nickel, and included all eczema phenotypes studied, but all allergens showed some evidence of benefit. This effect is most likely to be of benefit in those with strong reactivity to low concentrations of nickel in patch tests. This systematic review supports the conclusion that in those with recalcitrant eczema and patch test-confirmed nickel sensitization, low-nickel diets should be considered as a therapeutic option.